Acute and chronic musculoskeletal injury in para-sport: A systematic review - Ottesen, T.; Mashkovskiy, E.; Gentry, M.; Jensen, D.; Webborn, N.; Tuakli-Wosornu, Y. (Annals of Physical and Rehabilitation Medicine, 2018)
The health benefits of sport are myriad, but sport also carries an inherent risk of injury. This systematic review summarizes musculoskeletal injury epidemiology in elite and recreational para-athletes, and highlights research gaps. Material and method